(untitled) (Development Service Industry Management, 2025)
The article explores the theoretical and methodological foundations of business process management (BPM) as a modern approach to enterprise governance aimed at enhancing efficiency, adaptability, and competitiveness in a dynamic market environment. The study examines the evolution of the process-based management paradigm, emphasizing its systemic and integrative nature. Particular attention is paid to the interpretation of business processes by prominent scholars and to the mechanisms of their identification, modeling, analysis, improvement, and control as fundamental stages of BPM implementation. The paper synthesizes the viewpoints of both international and Ukrainian researchers, whose contributions shaped the conceptual landscape of process-oriented management. Furthermore, the study outlines current trends in BPM development, such as digital transformation, customer-centricity, process automation, and the increasing role of analytics in decision-making. It is argued that the process approach allows organizations to optimize resource utilization, reduce transaction costs, improve product and service quality, and enhance client satisfaction. The interrelation between business process structures and the strategic objectives of enterprises is analyzed in detail. It has been established that process management is an integrated mechanism for implementing the enterprise strategy through specific processes, which allows to move from declarative strategic management to its practical implementation. The article concludes that process management constitutes a vital management technology, enabling enterprises to maintain flexibility and resilience, achieve operational excellence, and sustain long-term growth in the face of market volatility and technological change.